Motivação e comprometimento organizacional dos servidores técnicos administrativos do Centro de Ciências da Saúde UFSM - Lucca, Ieda Maria Rissetti (2014)
The choice of topic "motivation and commitment" resulted from the fact that there is a lack of empirical studies linking motivation and organizational commitment. Based on the model of multidimensional conceptualization of motivation of Gagné et al. (2010), postulated the theory of self-determination of Deci and Ryan (1985, 2000) and the model of Meyer and Allen (1991) for organizational commitment, adapted and validated in Brazil to the public service context by Grohmann, Cunha e Silinski (2013), this study aims to identify the relationship between motivational levels and the commitment of administrative technical Center Servers the Sciences of Health - UFSM. It was chosen by performing a descriptive research was chosen using the lifting of the survey type, with quantitative variables as described by Malhotra (2006). The population studied consisted of 168 technical administrative servers belonging to the three levels. The questionnaire had its structure based on two models proposed in the research. The results indicated that there is a statistically significant moderate relationship between motivation and commitment of the servers, being that it was possible to develop the profile of the respondents, where it was found that the variable sex was the most impacted in the motivation variables of education and position were the most impacted in commitment servers respondents the commitment of servers. The motivation had the lowest average (x = 3.10), almost neutral what needs to be improved urgently, since the commitment showed moderate average (x = 3.62) and also needs to be improved in a second time. To establish relations among the dimensions of the constructs, can be assert that the results demonstrated exist correlations very low, and affective commitment is not correlated with any of the dimensions of or the motivation and commitment. The results showed moderate correlations among the other dimensions of research. Through regression analysis it was found that the motivation for the work of servers administrative technical Center Servers the Sciences of Health the UFSM is an antecedent of organizational commitment with a moderate degree of dependence. It is hoped that this study may be useful for research correlated area of management of public institutions, since it works with this approach are scarce.